2017
DOI: 10.1371/journal.pone.0183303
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of human embryonic stem cells into corneal epithelial progenitor cells under defined conditions

Abstract: The development of cell-based therapies using stem cells represents a significant breakthrough in the treatment of limbal stem cell deficiency (LSCD). The aim of this study was to develop a novel protocol to differentiate human embryonic stem cells (hESCs) into corneal epithelial progenitor cells (CEPCs), with similar features to primary cultured human limbal stem cells (LSCs), using a medium composed of DMEM/F12 and defined keratinocyte serum-free medium (KSFM) (1:1) under different carbon dioxide (CO2) level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…Most previously published studies to generate corneal epithelial cells from hPSCs have relied on the use of undefined, xenogeneic factors such as conditioned medium, PA6 feeder cells, Bowman’s, or amniotic membranes [ 16 , 19 , 47 , 48 ]. A recent, defined protocol to differentiate a single hESC line to corneal epithelial progenitor cells utilized simple keratinocyte serum-free medium (KSFM) mixed with DMEM/F12 for increased calcium concentration, together with a simple col IV matrix [ 30 ]. ABCG2- and p63-positive populations were produced in just 6 days but differentiation required elevated CO 2 levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most previously published studies to generate corneal epithelial cells from hPSCs have relied on the use of undefined, xenogeneic factors such as conditioned medium, PA6 feeder cells, Bowman’s, or amniotic membranes [ 16 , 19 , 47 , 48 ]. A recent, defined protocol to differentiate a single hESC line to corneal epithelial progenitor cells utilized simple keratinocyte serum-free medium (KSFM) mixed with DMEM/F12 for increased calcium concentration, together with a simple col IV matrix [ 30 ]. ABCG2- and p63-positive populations were produced in just 6 days but differentiation required elevated CO 2 levels.…”
Section: Discussionmentioning
confidence: 99%
“…ABCG2- and p63-positive populations were produced in just 6 days but differentiation required elevated CO 2 levels. The mechanism behind these differentiation conditions was not discussed [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 28 In addition, CEC derived from hESC in DMEM/F12 mixed at 1:1 with keratinocyte serum-free medium under 7% O 2 are seeded on decellularized porcine limbal matrix followed by air-lift culture to induce epithelial stratification. 29 Although human DC is a better choice compared to the animal counterparts, as they possess human corneal properties and will not cause xenogeneic immune response, 30 the limited availability of the source still imposes a major hurdle to their use.…”
Section: Introductionmentioning
confidence: 99%
“…In case of differentiation of the iPSCs towards CE fate, collagen IV [ 47 ] has been demonstrated to be an ideal substrate. Interestingly, Zhang et al demonstrated that slightly elevated CO 2 was conductive to the differentiation of CE progenitors from hESCs [ 49 ]. However, the underlying mechanism remained unclear which points to the need for further standardization of the crucial parameters such as the compatibility of the substrate, nature of the pluripotent cells, and the media used for culturing the cells apart from the oxygen modulation.…”
Section: Derivation Of Corneal Epithelial Cell Phenotypes From Ipscsmentioning
confidence: 99%